Sustainable manufacturing for the future - a white paper - Jolly, Mark R. (Cranfield University, 2016)
First white paper on the future of Manufacturing in the Food and Drinks industry in Great Britain based on the outcomes of an Industry-Academia Workshop.
Keywords: 'Food and Drink Industry'; 'Sustainable Manufacturing'; 'Future Manufacturing 2050'